On the Case of Locke’s Limit of Free Speech, and Its Justification (Hasanuddin Journal of Strategic and International Studies (HJSIS), 2023)
John Locke’s Second Treatise exists as one of the fundamental concepts in modern political thoughts, acting as a basic foundation of liberalism at its early stages due to its core concepts focusing around freedom of speech and expression. His understanding of said freedom, however, comes with a limit centred around both direct and indirect harm, which acts as this article’s main point of interest. The author argues that Locke’s implementation of a limit on free speech does not impede the people’s freedom at all, but instead serves to create an environment where every opinion matters, no matter the origin, be it from a majority or minority. To support this argument, the author has put forth three claims based around several parts of the Second Treatise, along with case studies relating to them. As a result, Locke’s emphasis on the limits of free speech advocated for a wide-ranging opportunity for everyone to declare their opinions freely and openly, necessitating vigorous debates between opinions without resulting in friction between differing groups, acting as a tool for progress instead of conflict. To conclude, Locke reveals a nuanced understanding of freedom of speech while highlighting its role as a cornerstone of early liberalism while acknowledging limits around harm, and contending that his imposition of boundaries fosters inclusive environment while encouraging debates between opinions, and ultimately promotes progress in a society.